Validation of a Short-Form Five Facet Mindfulness Questionnaire Instrument in China - Meng, Yong; Mao, Kaixian; Li, Chaoping (Frontiers in Psychology, 2020)
The Five Facet Mindfulness Questionnaire (FFMQ) developed by Baer and colleagues has been widely used owing to its satisfactory psychometric properties. Because there was not yet a short-form version of the FFMQ (SF-FFMQ) that could be utilized in work settings available in China, we developed a Chinese SF-FFMQ. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) supported a five-factor structure of our Chinese SF-FFMQ in two Chinese samples (Sample 1, N = 535; Sample 2, N = 391). The internal consistencies of the facets and the whole scale were acceptable. The predictive validity of this questionnaire was affirmed. Overall, the mindfulness facets correlated with related constructs including depression symptoms, anxiety symptoms, employee life well-being, employee workplace well-being, and employee psychological well-being. In sample 2, which consisted of participants employed by local companies, we found that mindfulness mediated a positive relationship between servant leadership and employees’ satisfaction with work-family balance. In conclusion, our Chinese SF-FFMQ was found to be a valid and reliable measurement tool and our results support its use in both research and practice in clinical and work settings in China.